Feasibility and outcomes of integrating continuous quality improvement measures in infection prevention and control interventions at selected health facilities in Nairobi, Kenya during the COVID-19 pandemic, 2020 – 2021 - Wangusi, Rebeccah; Wafula, Sam; Amadi, Emmanuel; Orawo, Joshua; Momanyi, Emmah; Ondigo, Joram; Ndichu, Geoffrey; Lascko, Taylor; Lavoie, Marie-Claude; Rarriw, Patricia; et al. (International Journal of Infection Control, 2025)
Background: Infection prevention and control (IPC) programs are critical for safe, high-quality, and people-centered care. While the effect of IPC in averting Healthcare-associated infections (HAIs) is not in contention, the intervention models to promote IPC performance are little understood in developing countries such as Kenya. This study tested the feasibility of integrating continuous quality improvement (CQI) approaches in IPC measures and the resultant performance of IPC uptake in selected PEPFAR-supported health facilities in Nairobi, Kenya. Methods: We conducted a baseline assessment (October 2020–December 2020) followed by quarterly assessments over 9 months (January 2021–September 2021) to assess the uptake of IPC practices upon implementation of IPC interventions through a CQI approach. The assessment was done in 49 health facilities in Nairobi, Kenya. The IPC interventions included the following: triage and screening; policies and training; supplies; Tuberculosis (TB) clinic measures; laboratory measures; injection safety; environmental cleaning; and device processing. Each of these interventions had specific activities that were tracked during the assessment. Specific CQI programs at each facility were developed to address gaps observed during baseline assessments, such as hand hygiene, healthcare worker screening, waste management, and triaging. Results: All 49 facilities implemented interventions to improve IPC under a CQI program but only 40 had data available regarding CQI activities. During the assessment period, mean scores for all IPC domains increased across all 49 facilities. There were significant improvements across all domains with the highest improvements recorded in the domains of policies, coordination, and training (from 15 to 100%; p < 0.001), patient screening, and triage (45 to 100%; p < 0.001), TB clinic measures (38 to 86%; p < 0.001), and healthcare worker screening and triage (35 to 72%; p < 0.001). Conclusion: IPC interventions, using a CQI approach, improved IPC mean scores substantially during the assessment period. Evidently, integrating CQI has an additive and significant effect on IPC uptake.